Ginger and its relationship with foreign trade in the Peruvian economy 2010 – 2019 - Cisneros-Santos, Gregorio (2021)
Ginger (Zingiber officinale), better known as kion, has become an emblematic product of the exportable offer, with advantages and functional properties that are highly appreciated in the international market, with very notable official figures in 2019, placing Peru as the fourth exporting country world with 23.4 thousand tons and 41.5 million US $. The objective of this research work was to determine the influence of ginger exports on foreign trade in the Peruvian economy in the period 2010 - 2019; For this, the development of ginger exports was analyzed, as well as its trend, relating it to the behavior of the Gross Domestic Product and the Agricultural GDP, using secondary sources. The descriptive and correlational level study evaluated the significant relationship between indicators, using deductive and inductive methods. After the corresponding analysis, it was possible to determine a high correlation between ginger exports and total exports (R2 = 0.6794); as well as with non-traditional exports (R2 = 0.7296); similarly, a high relationship with the growth of our economy, which is evidenced in the correlation with the National Gross Domestic Product (R2 = 0.7971); and the Gross Domestic Agricultural Product (R2 = 0.6885). It is concluded that the export of ginger constitutes an important factor in the growth of foreign trade in the national economy.